Apoio social e qualidade de vida de famílias de crianças com cardiopatia congênita - Silva, Gisele Vilella Da [UNIFESP] (2018)
Objective: To evaluate to what extent social support for parents (caregivers) of children with congenital heart diseases impacts their quality of life. Methods: Crosssectional study, with 254 parents of children with congenital heart diseases. Data were collected by semi structured interview, patient’s clinical data, socioeconomic status, questionnaire quality of life scale WHOQOLBREF and the scale of social support MOS. Results: Receiving social support was correlated with quality of life (Pearson’s r = 0.535; p < 0.001). In a multiple linear regression model, for each point more on the MOS scale there was a significant increase in the total scale score WHOQOLBREF (β= 0.30; IC 95%: 0.23; 0.37). Socioeconomic conditions were associated with quality of life scale (β = 0.27; IC 95%: 0.11; 0.43). Caregivers who reported not having leisure activity (β= 3.27; IC 95% 5.55; 1,12) and who were in health treatment (β = 2.86; IC 95%: 5.55; 0,17) had a lower perception on the WHOQOLBREF scale. Conclusions: Taking care of a child with congenital heart disease entails negative consequences, which can be intensified by lack of leisure activity and having health problems. Receiving social support and having sufficient socioeconomic resources positively influences the quality of life.